Application Of Woolwich Massage To Increasing Breast Milk Production In Post Partum Mothers At Pmb Cahyati, S.Tr. Long Parung Keb Year 2023 - Tri Antika, Selvia; Rismayanti, Tetin (CV. Inara, 2024)
Background: Coverage Of Infants Who Received Exclusive Breastfeeding In Bogor City In 2018 Was 45.42% Then In 2019 It Increased By 53.12%, In 2020 It Decreased By 51.06% And In 2021 It Decreased Again, Namely 48.58% Of 1860 Babies Examined. The Decrease In Exclusive Breastfeeding In Infants In 2021 Shows That There Is A Lack Of Concern And Awareness Of Mothers And Families About The Importance Of Breast Milk. Efforts That Can Be Made To Increase Breast Milk Production By Doing Massages Such As Woolwich Massage. Research Objective To Find Out Whether Woolwich Massage Can Increase Breast Milk Production In Postpartum Mothers. Research Method: This Study Used A Pre-Experimental Design Research Method With A Pre-Test And PostTest One Group Research Design. The Research Sample Of 18 Respondents Was Taken With Total Sampling Technique. Research Results: Based On The Results Of Statistical Tests Using The Sample Paired T-Test, The P-Value = 0.001 <0.05 Was Obtained. This Means That There Is An Effect Of Woolwich Massage On Increasing Breast Milk Production Of Postpartum Mothers At Pmb Cahyati, S.Tr. Keb Parung Panjang Bogor In 2023. Suggestion: It Is Expected That Mothers Start Doing Breast Care Since Pregnancy By Applying Woolwich Massage And Immediately After Birth To Immediately Do Imd As One Way To Increase Breast Milk Production So That Mothers Can.